2018
DOI: 10.1021/acs.chemrev.8b00081
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine Organocatalysis

Abstract: The hallmark of nucleophilic phosphine catalysis is the initial nucleophilic addition of a phosphine to an electrophilic starting material, producing a reactive zwitterionic intermediate, generally under mild conditions. In this Review, we classify nucleophilic phosphine catalysis reactions in terms of their electrophilic components. In the majority of cases, these electrophiles possess carbon–carbon multiple bonds: alkenes (section 2), allenes (section 3), alkynes (section 4), and Morita–Baylis–Hillman (MBH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
303
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 864 publications
(310 citation statements)
references
References 1,070 publications
(1,430 reference statements)
4
303
0
3
Order By: Relevance
“…Tertiary phosphines are unique and diverse Lewis bases that are widely used in many areas of synthetic chemistry. Applications range from their utilization as ubiquitous ligands in coordination or organometallic chemistry to phosphine‐catalyzed and stoichiometric phosphine‐mediated transformations. One of the main reasons for their broad range of applications is the intriguing ease with which the steric and electronic properties of phosphines can be rationally tuned using various substituents .…”
Section: Figurementioning
confidence: 99%
“…Tertiary phosphines are unique and diverse Lewis bases that are widely used in many areas of synthetic chemistry. Applications range from their utilization as ubiquitous ligands in coordination or organometallic chemistry to phosphine‐catalyzed and stoichiometric phosphine‐mediated transformations. One of the main reasons for their broad range of applications is the intriguing ease with which the steric and electronic properties of phosphines can be rationally tuned using various substituents .…”
Section: Figurementioning
confidence: 99%
“…The remarkable ability of phosphines to act as nucleophilic catalysts of many different organocatalytic transformations is well‐recognized . Historically, this activation mode has been utilized to develop new organocatalytic higher‐order cycloadditions with the participation of tropone‐derived systems as higherenes for the first time.…”
Section: Troponoid Systems In Organocatalytic Higher‐order Cycloadditmentioning
confidence: 99%
“…[5] In this vein, recent work by the groups of Shibata and Cahard, [6] Liu, [7] and Zhao [8] reflects the synthetic potential of this approach by the use of phosphorus derivatives as oxygen acceptors,a llowing access to valuable and reactive sulfenyl electrophiles from the more readily handled sulfonyl congener. [10,11] In this context, we have shown that af our-membered phospha-Figure 1. These undesirable characteristics are exacerbated by the fact that the P III reagent, itself ap otent nucleophile,c onsumes the electrophilic sulfenyl donor in competition with the target substrate to give undesired thiophosphonium ions ( Figure 1B).…”
mentioning
confidence: 96%
“…[10,11] In this context, we have shown that af our-membered phospha-Figure 1. [10,11] In this context, we have shown that af our-membered phospha-Figure 1.…”
mentioning
confidence: 96%
See 1 more Smart Citation